Answer :

Let a be the first term and d be the common difference.

Given: a7 = - 4


a13 = - 16


Now, Consider a7 = - 4


a + (7 - 1)d = - 4


a + 6d = - 4 ……….(1)


Consider a13 = - 16


a + (13 - 1)d = - 16


a + 12d = - 16 ……….(2)


Now, subtracting equation (1) from (2), we get,


6d = - 12


d = - 2


from equation (1), we get,


a = - 4 - 6d


a = - 4 - 6 × (-2)


a = - 4 + 12


a = 8


Thus the AP is a, a + d, a + 2d, a + 3d, a + 4d,….


Therefore the AP is 8, 6, 4, 2, 0,….


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses